Cytokine kinetic profiles in children with acute lower respiratory tract infection: a post hoc descriptive analysis from a randomized control trial. (December 2018) - Fuchs, A.; Gotta, V.; Decker, M.-L.; Szinnai, G.; Baumann, P.; Bonhoeffer, J.; Ritz, N.; ,
Abstract: Objectives: Standard inflammatory markers and chest radiography lack the ability to discriminate bacterial from non-bacterial lower respiratory tract infection (LRTI). Cytokine profiles may serve as biomarkers for LRTI, but their applicability to identify aetiology, severity of disease and need for antibiotic prescription in children remains poorly defined. Objectives were to determine the cytokine kinetic profiles over 5 days in paediatric patients with LRTI, to investigate the relationship between cytokine patterns, and clinical and laboratory variables. Methods: We included patients aged 1 month to 18 years, with febrile LRTI and three consecutive cytokines measurements on days 1, 3 and 5 of a randomized controlled trial (ProPAED study). We evaluated differences in cytokine concentrations between days and associations with clinical and laboratory variables. Results: A total of 181 patients (median age 4.1 years) were included; 72/181 (40%) received antibiotics. Serum concentrations of interferon (IFN)-γ, interleukin (IL)-1ra, IL-6, IL-10, IFN-γ-inducible protein (IP)-10 and tumor necrosis factor-α were elevated on day 1 and decreased subsequently, with the greatest decline between day 1 and 3 (by −8 to >−94%). Procalcitonin (PCT) and C-reactive protein (CRP) values showed a protracted decrease with the most prominent reduction in concentrations between days 3 and 5. Significantly elevated IL-6 concentrations were associated with hospital admission, antibiotic treatment, and prolonged antibiotic treatment. Bacteraemic LRTI patients had higher concentrations of IL-1ra (p <0.0055) and IL-6 (p <0.0055) on day 1. Conclusions: We observed an earlier decrease of elevated cytokines compared to PCT or CRP. Both pro- and anti-inflammatory cytokines may serve as markers for severity of LRTI.